2020
DOI: 10.2217/imt-2020-0105
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio in Prognosticating Immunotherapy Efficacy

Abstract: Aim: To examine neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in prognosticating immunotherapy efficacy. Methods: A retrospective study of 156 patients with metastatic melanoma and non-small-cell lung cancer on PD-1 inhibitors. Results: Baseline NLR ≥5 was associated with worse progression-free survival (hazard ratio [HR]: 1.53; 95% CI: 1.01–2.31; p = 0.043) but nonsignificant worse overall survival trend (HR: 1.51; 95% CI: 0.98–2.34; p = 0.064). PLR ≥200 was associated with worse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
2
24
1
Order By: Relevance
“…Platelets induce epithelial-to-mesenchymal migration of circulating tumor cells and promote tumor cell extravasation and metastasis (Schumacher et al, 2013;Copija et al, 2020). It is reported high NLR and PLR are associated with poor outcome and are useful predictors of the efficacy of anti-PD-1 therapy in many cancers (Dharmapuri et al, 2020;Kartolo et al, 2020). In this study, we found that PLR only was the factor influencing PFS in univariate analysis for patients treated with anti-PD-1 therapy in GC and CRC.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Platelets induce epithelial-to-mesenchymal migration of circulating tumor cells and promote tumor cell extravasation and metastasis (Schumacher et al, 2013;Copija et al, 2020). It is reported high NLR and PLR are associated with poor outcome and are useful predictors of the efficacy of anti-PD-1 therapy in many cancers (Dharmapuri et al, 2020;Kartolo et al, 2020). In this study, we found that PLR only was the factor influencing PFS in univariate analysis for patients treated with anti-PD-1 therapy in GC and CRC.…”
Section: Discussionmentioning
confidence: 64%
“…NLR was calculated as absolute neutrophil count/total lymphocyte count; MLR was calculated as monocyte count/total lymphocyte count; and PLR was calculated as platelet count/total lymphocyte count. The cutoff value for NLR was 5 in accordance with previous studies (Kartolo et al, 2020;Ueda et al, 2020); the optimal cutoff values for MLR and PLR were 0.31 and 135, respectively, which were determined using R-4.0.2 software (R Core Team, 2014). The chi-squared test and Fisher's exact test were used to assess relationships among categorical variables.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, owing to the absence of biomarkers able to predict response that would guide the therapeutic choice, we investigated the correlations between therapy outcomes and both clinical and blood parameters. The role of simple blood parameters was previously explored in a cemiplimab series ( 22 ) showing a predictive value of the absolute lymphocyte count and was established in various cancer settings ( 25 ) in which specific white cells and their ratios, like neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), were shown to mirror the complex interplay between thrombosis, inflammation, and immunosuppression ( 26 , 27 ). Thus, we assessed the predictive role of blood count both as pre-treatment value and as longitudinal variations.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil-to-lymphocyte ratio at 6 weeks post treatment in patients with advanced NSCLC was able to predict PFS after anti-PD-1/PD-L1 treatment [ 25 ]. Moreover, high baseline NLR and high baseline PLR were both associated with worse immunotherapy efficacy regardless of cancer type, especially in metastatic melanoma and NSCLC [ 26 ].…”
Section: Discussionmentioning
confidence: 99%